ETIKA JURNALISTIK DALAM PROSES PELIPUTAN BERITA - Lesmana, Fanny (Scriptura, 2015)
One of the activities carried out by journalists in their profession is covering the story. In the process of news reporting is done through personal initiative, assignment editors and invitations in the form of press conferences and press releases, journalists extremely vulnerable from the state to not abide by the code of professional conduct bears. Adherence to the Kode Etik Jurnalistik is a thing that should be done by journalists in Indonesia. However, educational or professional background, attitudes or beliefs held and meterialistik factors, as well as the speed issue makes a journalist is not easy to adhere to the Code of Ethics of Journalism although it is strongly associated with the moral responsibility of the journalist and the credibility of the media where journalists take shelter. Therefore, the company needs a firmness of the press in the pattern of recruiting journalists, conducting the training, and put the ideals on themselves journalists when they carry out the Kode Etik Jurnalistik, in particular in the process of news coverage.